Novelties in Phyllanthus sect. Phyllanthus subsect. Phyllanthus (Phyllanthaceae): two new species, two new synonyms, and a lectotype - Torres, Alícia Marques [UNESP]; da Silva, Marcos José (Wiley, 2024)
An ongoing taxonomic work on Phyllanthus subsect. Phyllanthus, resulting from the analysis of protologues and the study of approximately 2000 collections, including all types, historical collections, and observations in the field, led us to describe two new species (P. lobatus and P. platystigma), and to propose the synonymization of P. mimicus and P. bolivianus under P. niruri, as well as establish a lectotype for P. bolivianus. For both new species, we provide, descriptions, illustrations, preliminary conservation status, flowering and fruiting periods, environmental preferences and images in their habitat. In addition, they are compared with morphologically similar congeners and their systematic position is discussed.
Keywords: Brazilian Flora; nomenclature; Phyllantheae; taxonomy